E-Module Development Using Professional 3D Pageflip on Negotiation Materials - Trisman Harefa; Tuti Marnis Laoli (Edumaspul: Jurnal Pendidikan, 2022)
The aims of this study were to (1) develop e-module media using 3D Pageflip Professional on negotiation materials, (2) find out the feasibility of e-modules by material experts, linguists and media experts, (3) find out the practicality of e-modules through trials. individual, small group trials, and field trials, (4) determine the effectiveness of e-modules through the results of student evaluations. This study was developed using a 4D model consisting of four stages, namely definition, planning, development, and dissemination. Based on the results of the study, it can be concluded that the results of the validation by material experts were in the first revision 58.6%, the second revision 75% and the last revision 97%. The results of validation by linguists in the first revision were 60.7%, the second revision was 82% and the last revision was 96%. The results of the validation by media experts at the first revision were 50%, the second revision was 70% and the last revision was 93%. The results of individual trials are 50%, small group trials, 80%, and field trials 97.8%. The results of completeness obtained in the final evaluation reached 100% completeness. So, it can be concluded that the e-module media that has been developed by researchers can be said to be feasible, practical and effective as a learning reference in various schools. The suggestion from the researcher is that through the e-module media students are more motivated to learn and this media can also be useful for educators when teaching.